Belle eaudiobook An amish retelling of beauty and the beast. - Price, Sarah (Amish Fairytale, 2017)
To most townsfolk, he's known simply as The Beast. Annabelle Beiler has little interest in gossip, but she's heard about Adam Herschberger's scars and his gruff, solitary ways. Though he sounds like a character from one of Belle's treasured books, the man is real and, it turns out, just as unreasonable as the rumors claim. When a buggy accident wipes out the last of her daed 's money, forcing him to sell their farm, Adam buys it. Then he offers Belle a deal—marry him, and her family can keep their home. Everyone is shocked by Belle's decision, but she's determined to be a good fraa , cleaning Adam's rundown house and tending the overgrown garden. Breaking through her new husband's icy reserve will be another matter. Belle's courage and strength are abundant, but it will take true faith to guide Adam back to the heart of his Amish community—and to the loving marriage they both deserve. Contains mature themes.